Discharge and entrepreneurship in the preventive restructuring directive - Arias Varona F. Javier; Niemi Johanna; Hupli Tuomas (John Wiley & Sons Ltd., 2022)
The European Council adopted the Preventive Restructuring Directive (2019/1023/EU) on June 20, 2019, which must be transposed by July 17, 2021, subject to a possible extension of a maximum of 1 year for countries encountering particular difficulties in the implementation. The Directive signals a paradigm shift in EU policy on insolvency from the traditional focus on cross-border issues. The new Directive puts insolvency squarely at the heart of internal market regulation, following the EU's policy since the Great Recession of 2008 of promoting and strengthening the economy. Since 2016, the European Commission has issued several documents to facilitate insolvency procedures, leading to the recently adopted Preventive Restructuring Directive. Besides restructuring, the Directive promotes the discharge of pre-insolvency debt for entrepreneurs. The Directive does not require that discharge be extended to other natural persons but recommends it. This article discusses the relationship between entrepreneurs and non-entrepreneurs in an insolvency situation and concludes that a fair interpretation of the new Directive requires that the situation of the ordinary person with liability for business debt be closely scrutinised.